TCUP: A Novel hAT Transposon Active in Maize Tissue Culture - Smith, Alan; Hansey, Candice; Kaeppler, Shawn (Frontiers in Plant Science, 2012)
Transposable elements are capable of inducing heritable de novo genetic variation. The sequences capable of reactivation, and environmental factors that induce mobilization, remain poorly defined even in well-studied genomes such as maize. We treated maize tissue culture with the demethylating agent 5-aza-2-deoxcytidine and examined long-term tissue culture lines to discover silenced transposable elements that have the potential to induce heritable genetic variation. Through these screens we have identified a novel low copy number hAT transposon, Tissue Culture Up-Regulated (TCUP), which is transcribed at high levels in long-term maize Black Mexican Sweet (BMS) tissue culture and up-regulated in response to treatment with 5-aza-2-deoxycytidine. Analysis of the TIGR Maize Gene Index revealed that this element is the most frequently represented EST from the BMS cell culture library and is not represented in other tissue libraries, which is the basis for its name. A full-length sequence was assembled in inbred B73 that contains the putative functional motifs required for autonomous movement of a hAT transposon. Transposon display detected movement of TCUP in two long-term tissue cultured cell lines of the genotype Hi-II AxB and BMS. This research implicates TCUP as a transposon that is capable of reactivation and which may also be particularly sensitive to the stress of the tissue culture environment. Our findings are consistent with the hypothesis that epigenetic alterations potentiate genomic responses to stress during clonal propagation of plants.